2019
DOI: 10.2903/sp.efsa.2019.en-1551
|View full text |Cite
|
Sign up to set email alerts
|

Literature review in support of adjuvanticity/immunogenicity assessment of proteins

Abstract: Based on the risk assessment of genetically modified plants, according to Implementing Regulation (EU) No 503/201321 "In cases when known functional aspects of the newly expressed protein or structural similarity to known strong adjuvants may indicate possible adjuvant activity, the applicant shall assess the possible role of these proteins as adjuvants". To further investigate the topic, an EFSA procurement was launched requesting a comprehensive literature review and critically appraisal on adjuvanticity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 263 publications
0
22
0
Order By: Relevance
“…The Panel has previously evaluated the safety of Cry1A.105, Cry2Ab2 and Cry1Ac proteins, and no concerns on adjuvanticity were identified in the context of the applications assessed (see Table ). More recently, this aspect has been discussed in detail by EFSA (EFSA et al., ; Parenti et al., ). The levels of the individual Bt proteins in the four‐event stack soybean are comparable to those in the respective single soybean events (see Section 3.4.3).…”
Section: Assessmentmentioning
confidence: 99%
“…The Panel has previously evaluated the safety of Cry1A.105, Cry2Ab2 and Cry1Ac proteins, and no concerns on adjuvanticity were identified in the context of the applications assessed (see Table ). More recently, this aspect has been discussed in detail by EFSA (EFSA et al., ; Parenti et al., ). The levels of the individual Bt proteins in the four‐event stack soybean are comparable to those in the respective single soybean events (see Section 3.4.3).…”
Section: Assessmentmentioning
confidence: 99%
“…The Panel has previously evaluated the safety of Cry1A.105, Cry2Ab2, Vip3Aa20 and Cry3Bb1 proteins, and no concerns on adjuvanticity were identified in the context of the applications assessed (see Table ). More recently, this aspect has been discussed in detail by EFSA (EFSA, ; Parenti et al., ). The levels of the individual Bt proteins in the four‐event stack maize are comparable to those in the respective single maize events (see Section 3.4.1.4).…”
Section: Assessmentmentioning
confidence: 99%
“…Thus, in addition to cytotoxicity, the incidence of allergic reactions following novel protein consumption (e.g., from insect origin) has been assessed (Parenti, Santoro, Del Rio, & Franceschi, 2019). The majority of studies explored the proteins' immunomodulatory properties and their influence on inflammatory cytokine production, antibodies production, and lymphocyte activity and proliferation (Parenti et al, 2019). One study reported that oral administration of carp egg protein hydrolysates (CEPHs) (pepsin hydrolyzed) to female BALB/c mice significantly enhanced humoral immune response because immunoglobulin A (IgA) antibody production increase in serum.…”
Section: Allergenicitymentioning
confidence: 99%
“…Furthermore, a complete allergenicity risk assessment is needed (according to the European Food Safety Authority (EFSA) legislation) to approve novel protein sources as potential food ingredients taking into consideration various aspects such as route (e.g., oral) and dose of protein exposure, protein properties (e.g., physicochemical properties) and how protein is perceived by each person's immune system (Parenti et al, 2019). Different strategies can be used to assess allergenicity risks (Crevel et al, 2014;Fernandez, Mills, Koning, & Moreno, 2019).…”
Section: Allergenicitymentioning
confidence: 99%